An Endophytic Strain of Bacillus amyloliquefaciens Suppresses Fusarium oxysporum Infection of Chinese Wolfberry by Altering Its Rhizosphere Bacterial Community - Uwaremwe, Constantine; Yue, Liang; Wang, Yun; Tian, Yuan; Zhao, Xia; Liu, Yang; Zhou, Qin; Zhang, Yubao; Wang, Ruoyu (Frontiers in Microbiology, 2022)
Root rot disease is a serious infection leading to production loss of Chinese wolfberry (Lycium barbarum). This study tested the potential for two bacterial biological control agents, Bacillus amyloliquefaciens HSB1 and FZB42, against five fungal pathogens that frequently cause root rot in Chinese wolfberry. Both HSB1 and FZB42 were found to inhibit fungal mycelial growth, in vitro and in planta, as well as to promote the growth of wolfberry seedlings. In fact, a biocontrol experiment showed efficiency of 100% with at least one treatment involving each biocontrol strain against Fusarium oxysporum. Metagenomic sequencing was used to assess bacterial community shifts in the wolfberry rhizosphere upon introduction of each biocontrol strain. Results showed that HSB1 and FZB42 differentially altered the abundances of different taxa present and positively influenced various functions of inherent wolfberry rhizosphere bacteria. This study highlights the application of biocontrol method in the suppression of fungal pathogens that cause root rot disease in wolfberry, which is useful for agricultural extension agents and commercial growers.